Exploratory assessment of serological tests to determine antibody titer against SARS‐CoV‐2: Appropriateness and limits. Issue 5 (25th March 2022) - Colombini, Alessandra; Viganò, Marco; Tomaiuolo, Rossella; Di Resta, Chiara; Corea, Francesca; Sabetta, Eleonora; Ferrari, Davide; De Vecchi, Elena; Maria Spanò, Sestina; Banfi, Giuseppe
Abstract: Background: Serological tests can be used to detect antibodies in the serum of subject's after SARS‐CoV‐2 infection and vaccination. Currently, variability in antibody titers and the availability of a multiplicity of serological tests have made it necessary to highlight their appropriateness and limitations in various diagnostic settings. Methods: This study is part of Covidiagnostix, a multicenter project aimed at the assessment of the health technology used in SARS‐CoV‐2 serological tests. Based on data gained from the analysis of over 5000 subjects, a selected number of serum samples, representative of different diagnostic settings, were analyzed first by qualitative immunoassays (IgA, M, and G MILLIPLEX ® SARS‐CoV‐2 tests based on Luminex ® ) to define the immunoglobulins serum composition and subsequently by four serological diagnostic tests (Elecsys Anti‐SARS‐CoV‐2 and Elecsys Anti‐SARS‐CoV‐2 S by Roche, SARS‐CoV‐2 IgG by Siemens Healthcare, and CHORUS SARS‐CoV‐2 "NEUTRALIZING" Ab by DIESSE). The first WHO International Standard for SARS‐CoV‐2 was also analyzed using the same methods. Results: This study evaluated the antibody content and titer of the WHO Standard and serum of subjects with/without previous infection and before/after vaccination for SARS‐CoV‐2. Conclusion: The definition of antibodies in the WHO standard and the analysis of serum samples allowed for the identification of the appropriateness of serological tests in each diagnostic setting, increasing the effectiveness of the resulting laboratory data. Furthermore, we found that it would be optimal to produce new international standards against the S1 domain and RBD of the SARS‐CoV‐2 spike protein for a more effective serological monitoring of vaccination. Abstract : Correlation plot represents the correlation between the result of the serological tests and MILLIPLEX ® SARS‐ CoV‐2 Antigen Panels. The strength of the correlation is represented by dot color and size, according to the continuous bar reported in the figure.